A Blowout Jet Associated with One Obvious Extreme-ultraviolet Wave and One Complicated Coronal Mass Ejection Event - Miao, Yuhu; Liu, Yu; Li, Hong Bo; Shen, Yuan Deng; Yang, Shu Hong; Elmhamdi, Abouazza; Kordi, Ayman S.; Abidin, Zamri Zainal (American Astronomical Society, 2018)
In this paper, we present a detailed analysis of a coronal blowout jet eruption that was associated with an obvious extreme-ultraviolet (EUV) wave and one complicated coronal mass ejection (CME) event based on the multiwavelength and multi-view-angle observations from the Solar Dynamics Observatory and the Solar Terrestrial Relations Observatory. It is found that the triggering of the blowout jet was due to the emergence and cancellation of magnetic fluxes on the photosphere. During the rising stage of the jet, the EUV wave appeared just ahead of the jet top, lasting about 4 minutes and at a speed of 458-762 km s-1. In addition, obvious dark material is observed along the EUV jet body, which confirms the observation of a mini-filament eruption at the jet base in the chromosphere. Interestingly, two distinct but overlapped CME structures can be observed in corona together with the eruption of the blowout jet. One is a narrow jet shape, while the other one is a bubble shape. The jet-shaped component was unambiguously related to the outwardly running jet itself, while the bubble-like one might either be produced due to the reconstruction of the high coronal fields or by the internal reconnection during the mini-filament ejection according to the double-CME blowout jet model first proposed by Shen et al., suggesting more observational evidence should be supplied to clear the current ambiguity based on large samples of blowout jets in future studies.